Tempest in the Rankings Teapot: An African Perspective - Teferra, Damtew (International Higher Education, 2017)
According to the Times Higher Education, “the reputation league table is based on nothing more than subjective judgment.” QS also states that 60 percent of its scores are dependent on reputation, thus subjective. What is depressingly astonishing, however, is how seriously the world of higher education (and beyond) takes these self-serving businesses, which use defective and flawed instruments year in and year out. This piece provides yet another evidence on their utter failure in their purported role as gatekeepers of quality.